Examination of the effect of ovarian radiation injury induced by hysterosalpingography on ovarian proliferating cell nuclear antigen and the radioprotective effect of amifostine: an experimental study - Can, Behzat; Atilgan, Remzi; Pala, Sehmus; Kuloglu, Tuncay; Kiray, Sule; Ilhan, Nevin (Dove Medical Press Ltd, 2018)
Aim: The aim of this study was to examine the effect of amifostine on cellular injury in the ovarian tissue induced by hysterosalpingography (HSG). Methods: In total, forty 4-month old female Wistar Albino rats were assigned into 8 groups. Each group contained 5 rats. Group 1 (G1): rats were decapitated without any procedure. Group 2 (G2): rats were decapitated after 3 hours of total body irradiation. Group 3 (G3): rats were decapitated 3 hours after HSG procedure. Group 4 (G4): rats were decapitated 3 hours after HSG procedure performed 30 min after receiving amifostine 200 mg/kg intraperitoneally. Group 5 (G5): rats were decapitated after 1 month without any procedure. Group 6 (G6): rats were decapitated after 1 month of total body irradiation. Group 7 (G7): rats were decapitated 1 month after HSG procedure. Group 8 (G8): rats were decapitated 1 month after HSG procedure performed 30 min after receiving amifostine 200 mg/kg intraperitoneally. After rats were decapitated under general anesthesia in all groups, blood samples were obtained and bilateral ovaries were removed. One of the ovaries was placed in 10% formaldehyde solution for histological germinal epithelial degeneration, apoptosis and proliferating cell nuclear antigen scoring. The other ovary and blood sera were stored at -80 degrees C. TNF-alpha, total antioxidant status, total oxidant status, and malondialdehyde levels were studied in tissue samples and anti-mullerian hormone levels in blood samples. Results: At the end of the first month, there was significant ovarian germinal epithelium degeneration. Proliferating cell nuclear antigen immunoreactivity was significantly reduced in all other groups when compared with G1 and G5. Conclusion: In conclusion, amifostine could significantly reduce the ovarian cellular injury induced by HSG.
Keywords: hysterosalpingography; amifostine; ovarian damage; radiation